2019
DOI: 10.5688/ajpe7410
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Palliative Care in Pharmacy Education

Abstract: There is a growing need for palliative care pharmacists in the United States. There is also a gap in the education of palliative care for pharmacy students. To address both, pharmacy schools must develop and disseminate palliative care-focused experiences, including traditional didactic lectures, problembased learning, interactive skills, laboratory-and web-based experiences. This commentary presents the need for palliative care-focused experiences in the Doctor of Pharmacy (PharmD) degree program, and how sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[8][9][10] Corresponding author: Katie F. Leslie, PhD, MS Associate Professor, Sullivan University College of Pharmacy and Health Sciences 2100 Gardiner Ln., Louisville, KY 40205, USA Phone: 502-777-1667; Email: kleslie@sullivan.edu Deprescribing has gained increased attention in health sciences education with multiple calls for added content within curricula emphasizing opportunities for interprofessional learning experiences. [11][12][13][14] Specific to academic pharmacy, there is significant need to enhance teaching of optimal prescribing and deprescribing related content with student assessment measures in the didactic and experiential curricula. 12,15 In addition to educational content and evaluations, there are needs for further research into pharmacists' impact on deprescribing in end-of-life care settings, and to assess the need for and sustainability of palliative and hospice care pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Corresponding author: Katie F. Leslie, PhD, MS Associate Professor, Sullivan University College of Pharmacy and Health Sciences 2100 Gardiner Ln., Louisville, KY 40205, USA Phone: 502-777-1667; Email: kleslie@sullivan.edu Deprescribing has gained increased attention in health sciences education with multiple calls for added content within curricula emphasizing opportunities for interprofessional learning experiences. [11][12][13][14] Specific to academic pharmacy, there is significant need to enhance teaching of optimal prescribing and deprescribing related content with student assessment measures in the didactic and experiential curricula. 12,15 In addition to educational content and evaluations, there are needs for further research into pharmacists' impact on deprescribing in end-of-life care settings, and to assess the need for and sustainability of palliative and hospice care pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…This multipronged approach for all students is novel and aligns with the need for palliative care education for all students, as recently highlighted in pharmacy education. This educational need mirrors the growing need for palliative care pharmacists and the diverse roles that pharmacists may play in this setting 19‐21 . The role of the palliative care pharmacist includes direct patient care, counseling, patient advocacy, and education 21 .…”
Section: Discussionmentioning
confidence: 97%
“…56 Pruskowski et al reported that only 1% of the total curriculum time for pharmacists offers palliative care and end-of-life education. 57 There is also a gap in postgraduate opportunities, since the number of pain and palliative care postgraduate programmes is limited. 57 Furthermore, Xue et al showed in their study that about 59% of pharmacists had less than one year of experience working with patients with cancer, although they were well acquainted with pharmacology of pain.…”
Section: Discussionmentioning
confidence: 99%
“…57 There is also a gap in postgraduate opportunities, since the number of pain and palliative care postgraduate programmes is limited. 57 Furthermore, Xue et al showed in their study that about 59% of pharmacists had less than one year of experience working with patients with cancer, although they were well acquainted with pharmacology of pain. 58 The educational model for pharmacists is not adequate to prepare them for this type of care, hence several authors have organized strategies to develop necessary knowledge to teach clinical pharmacists about palliative care and the care of diseases that accompany elderly.…”
Section: Challenges In This Fieldmentioning
confidence: 99%